The Role of Women Kipang Cake Workers as a single parent in Tanjung Kipang Nagari Atar, Padang Ganting District, Tanah Datar Regency - Nur Halimah Halim; Wisroni Wisroni (Universitas Negeri Padang, 2023)
This research is background by the resilience of women as single parents in carrying out their roles as mothers and fathers for their children. The purpose of the study was to describe the role of female cake kipang workers as single parents in Tanjung Kipang Nagari Atar, Padang Ganting District, Tanah Datar Regency. The focus of the research is how the role of female kue kipang workers is as a single parent in educating children and also as the person in charge of the family economy. The research approach used is qualitative with the type of case study research. The research subjects were 2 female cake kipang workers who were single parents and their children, while the research informants were the family and closest neighbors of the research subjects. The research location is in Tanjung Kipang Nagari Atar, Padang Ganting District, Tanah Datar Regency. Data collection techniques used in-depth interviews and participatory observation. The results of the research on the role of women as single parents are as follows: first, the role of women as single parents in educating children. In educating children, the roles of women are: (1) Fulfilling psychological, social, and religious needs. The things that parents do to meet the psychological, social, and religious needs are: (a) Fulfilling the psychological needs of children by accompanying children to study at night at home, so that children do not feel lonely and ask how the children are even though the children are far from their parents. (b) Meeting social needs by involving children in solving problems that are being faced so that children can express their opinions and find solutions to the problems they are facing. (c) Meeting the religious needs of the child by reminding the child to always perform the five daily prayers and giving sanctions to the child when the child leaves the prayer. (2) Women as single parents become examples and models for children, namely parents invite children to carry out maghrib recitals so that children get used to doing it in the future. (3) Women as single parents in stimulating children's development, namely providing understanding to children about the condition of parents so that they can help parents and give responsibility to children to do homework. Second, the role of female kue kipang workers as single parents as the person in charge of the family economy. As the person in charge of the family economy, namely, (1) Working as a cake worker to be able to meet family needs and children's educational needs. (2) Doing other side jobs to increase income, namely working as farm laborers, raising cattle and also washing dishes at celebration events. (3) Regulating income in a frugal way so that the living needs and educational needs of children can be met properly. Keywords: The Role of Single Parent Women